Using Presentation Slide Media to Improve Student Learning Results on Fractional Number Material in Mathematics Lessons in Class 4 SDN 02 Cibadak - Budi Kurnia; Tia Siti Maryam; Amalia Listi Putri; Yusriyah Humaira; Muhammad Febriandi (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
The aim of this research is to characterize students' reactions to interactive slide presentation learning materials on fractions in Class 4 SDN 02 Cibadak, as well as media creation and its application. Utilizing the Borg and Gall paradigm, research and development is a research methodology. A questionnaire was used as a data collection tool. Saturated sampling was used to select a research sample consisting of 25 Class 4 students at SDN 02 Cibadak who represented the entire population. This media is in the very practical category, as evidenced by expert test findings which show that 91% of material experts, 85% of media experts and 89% of language experts think that this media is suitable. Based on their comments, teachers and students reported eligibility percentages that fell into the very practical category: 90% for students and 94% for educators. In short, this interactive PowerPoint learning resource for fractions is a great replacement for the traditional method of teaching fractions in elementary school mathematics classes (Class 4 SDN 02 Cibadak).